Role of scientific and special methods in military sciences researches - Shmakov О. М.; Drobakha G. А. (Honor and Law, 2019)
Attention is given to sometimes unjustified usage of special methods in military sciences researches that reduce the effectiveness of the latter. It is suggested to increase the role of scientific methods and thus to promote the level of researches of war and military science.